Management of anastomotic leaks after elective colorectal resections: The East of England experience. A retrospective cohort. (December 2021) - Aker, Medhat; Askari, Alan; Rabie, Mohamed; Aly, Mohamed; Adegbola, Samuel; Patel, Krashna; Currow, Chelise; Nunn, Rebecca; Hadjittofi, Christopher; Rankin, Adeline; Halai, Sonal; Elsamani, Karim; et al.
Abstract: Introduction: Colorectal anastomotic leaks (AL) are associated with high morbidity and mortality. Management of AL and its intra-operative decision making is often difficult. The aim of this multi-centre study is to explore different management strategies, including different surgical options, and analyse rates and patterns of failure of initial management. Methods: All consecutive patients who had a confirmed AL after elective colorectal resections from 1 st January 2014 to 31 st December 2019 were included at seven hospitals across the East of England Region. Morbidity (length of stay, and failures) and mortality were compared across the different management strategies, and survival analyses were performed (Clinicaltrials.gov ID: NCT05000580). Results: Across all seven hospitals, a total of 3391 elective resection were done during the study period. 201 (5.9%) consecutive patients with confirmed AL were included. The initial treatment was conservative in 102(50.7%). 19 patients (9.5%) had a radiological procedure, 80 (39.8%) of patients required surgery as an initial treatment post AL. Of those who initially did not have a surgical intervention (n = 121), 10% (n = 12/121) eventually required laparotomy, 2 additional patients required transanal drainage. Ultimately 45.8% (n = 92/201) of the whole population eventually required a laparotomy. Patients managed conservatively had a shorter LOS when compared to either radiological drainage or surgical patients. Patients with a defunctioning stoma are more likely to have a successful conservative management and shorter LOS. 90-day mortality across the entire population was 8.1%. There were no significant differences in mortality or long-terms survival between the different initial treatment modalities or whether the leak was right or left sided. Conclusion: Despite initial conservative, antibiotic and radiological intervention being successful in the majority of patients, two out of five patients will still require a laparotomy and over a quarter of patients will have an end stoma. Highlights: The study has highlighted the hazards of anastomotic leaks and the various potential options available for their management. Initial management is initially guided by the patient's haemodynamic status. Surgical options include anastomosis-sparing with diversion and, anastomosis-sacrificing procedures. In rectal leaks, the presence of a defunctioning stoma improves the likelihood of success of conservative management. Selecting the appropriate initial management for the appropriate patient is key. Over a quarter of patients who experiences an AL will ultimately have a stoma.